The effects of apricot resin addition to the light weight concrete with expanded polystyrene - Bicer, Ayse; Kar, Filiz (Taylor & Francis Ltd, 2017)
In this paper, the employability of waste Expanded Polystyrene Foam (EPS) as aggregate in production of concrete with apricot resin-added cement has been examined. The EPS ratios were determined as 20, 40, 60 and 80% of the total volume in the mixtures. The amount of the resin in the mixture is 1% of the weight of the total cement and EPS. At the end of 28days of drying period, the samples were subjected to certain tests to find out their physical properties. It was seen that the porosity had increased 3.0-26.38% times compared to the case with no resin. Similarly, with increasing the EPS ratio in the mixture from 20 to 80%, the density, thermal conductivity and compressive strength had decreased in the percentages of 14.66-17.61%, 15.49-17.43% and 17.58-40.32% respectively. The rate of water absorption of sample was less than 30%. From this results, it is concluded that these materials can be used as partition walls, floorings, ceiling concretes, briquettes or bricks and plaster instead of building-carrier systems such as columns or beams.
Keywords: Expanded polystyrene; apricot resin; light concrete; insulation plaster